Diversity and occurrence of major diseases of vegetables and fruit crops during spring season at Aanbukhaireni rural municipality of Tanahun district, Nepal - Subedi, Subash; Koirala, Sheela; Neupane, Saraswati (Journal of Agriculture and Natural Resources, 2019)
A survey has been conducted to assess the diversity and occurrence of major vegetables and fruits cultivated in Aanbukhaireni rural municipality of Tanahun district, Nepal during spring season of 2019.The surveyed areas were Satrasayaphant, Baradiphant and Dumridanda villages of ward no 1, Yeklephant, Markichowk and Pateni villages of ward no2 , Gaadapani village of ward no 3, Saakhar village of ward no 4 and Ghummaune village of ward no. 5. The surveyed area consists of upper tropical and sub tropical climate. The total no of farmers field selected for the survey was 34, 32, 24, 17 and 21 from ward no 1,2,3,4 and 5 respectively.The major vegetables cultivated during survey period in the surveyed area were bean, bitter-gourd, brinjal, chilli, cowpea, cucumber, okra, pumpkin, sponge-gourd, tomato, snake-gourd and bottle-gourd. Similarly, the fruits found in the region were banana, papaya,  grapes, mango, litchi, peach, guava, lemon, mandarin orange etc. The major diseases of vegetables noticed were early blight, late blight, cercospora leaf spot, powdery mildew, downey mildew, fruit rot, bacterial wilt, bacterial spot, leaf curl and mosaic. In case of fruits, sigatoka leaf spot,  panama wilt, black rot, algal leaf spot, canker, root rot, foot rot, sooty mold, red rust, anthracnose, rust, mosaic, alternaria leaf spot, downey mildew and leaf curl were the major diseases. The higher disease incidence (70%) and severity (48%) in vegetables were recorded in ward no 2 where as the lower incidence (45.2%) and severity (37.71%) were found in ward no 4. Similarly, the higher fruit disease incidence (70.24%) and severity (51.27%) in ward no 1 followed by ward no 2 with disease incidence and severity of 66.79% and 45.14% respectively. The reasons for those results are low educational level, lack of best bet technology, no proper irrigation and fertilizer, unavailability of pesticides for controlling the diseases. This study will be useful to identify the major diseases of vegetables and fruits of terai and inner terai region of Nepal and applying control measure, looking for the best possible solutions.